Interstitial pre-hispanic landscapes: Urban nature and archaeoastronomical heritage in Ñaña, Lima - Del Castillo Cáceres, Juan Manuel (2019)
The purpose of this research is to analyse the landscape and archaeoastronomical heritage of Ñaña, Lurigancho-Chosica, which subsists in the interstices of the contemporary urban periphery of Metropolitan Lima. Despite the state’s neglect and unregulated urban growth in its surroundings, it holds many unexploited attributes. The Union-Ñaña archaeological zone was inhabited since pre-Hispanic times by specialists in the observation of astronomical phenomena called yañac, who were linked to the cult of the snow peak Pariacaca. The latter was the most important apu from the Central Andes of Peru, according to the mythical 'Manuscript of Huarochirí' from the 16th century. Thus, the study of the relationship between landscape and astronomical alignments (a key aspect of the Andean worldview) is a crucial component of the following study, which also has the goal of expanding the understanding of the original function and future potential of these ancient sites associated to the Inca Road Network of the Rimac Valley. An increase in the degree of multi-disciplinary research employed appears as a variable to be evaluated; such research deepens these findings and builds the foundations for future environmental and cultural development policies in the study area. The results shown are the product of extensive fieldwork and context-mapping using ARC GIS, Stellarium and SunCalc software.